Geometric Evaluation of Mobile-Phone Camera Images for 3D Information - Ferruh Yilmazturk; Ali Ersin Gurbak (International Journal of Optics)
This study aimed to investigate the usability of smartphone camera images in 3D positioning applications with photogrammetric techniques. These investigations were performed in two stages. In the first stage, the cameras of five smartphones and a digital compact camera were calibrated using a calibration reference object, with signalized points having known three-dimensional (3D) coordinates. In the calibration process, the self-calibration bundle adjustment method was used. To evaluate the metric performances, the geometric accuracy tests in the image and object spaces were performed and the test results were compared. In the second stage, a 3D mesh model of a historical cylindrical structure (height = 8 m and diameter = 5 m) was generated using Structure-from-Motion and Multi-View-Stereo (SfM-MVS) approach. The images were captured using the Galaxy S4 smartphone camera, which produced the best result in the geometric accuracy tests for smartphone cameras. The accuracy tests on the generated 3D model were also applied in order to examine 3D object reconstruction capabilities of imaging with this device. The results demonstrated that smartphone cameras can be easily used as image acquisition tools for multiple photogrammetric applications.